Bridging the Gap across the Transition to Coparenthood: Triadic Interactions and Coparenting Representations from Pregnancy through 12 Months Postpartum - Kuersten-Hogan, Regina (Frontiers in Psychology, 2017)
Most family researchers agree that the coparenting relationship emerges some time during the transition to parenthood, though it is unclear whether it originates in pregnancy. Previous studies demonstrated that couples’ positive representations of their future coparenting relationship and harmonious coparenting behaviors observed during prenatal triadic interactions predicted better postpartum functioning. However, previous studies did not simultaneously assess prenatal coparenting behaviors and representations as predictors of postpartum coparenting. If the coparenting relationship originates during pregnancy, these behavioral and cognitive aspects of prenatal coparenting should show associations with their postpartum counterparts. Based on family systems-, attachment-, and social-learning theory, the first aim in this study was to explore whether prenatal coparenting representations and behaviors are associated with postpartum coparenting, which would suggest that both cognitive and behavioral aspects of the coparenting relationship emerge during pregnancy. A second aim was to determine whether parental coparenting representations are consistent with concurrently observed coparenting behaviors. A sample of 55 couples expecting their first child was observed during triadic interactions during pregnancy and at 3- and 12-months postpartum. Observations were coded using the Coparenting and Family Rating System. Composite scores were formed to reflect harmonious and antagonistic coparenting behaviors. Parents’ representations of harmonious and antagonistic coparenting were assessed via interviews and questionnaires during pregnancy and at 3- and 12-months postpartum. Results indicated that prenatal representations of harmonious and antagonistic coparenting were associated with and predicted unique variance in respective postpartum coparenting representations. Prenatal coparenting behaviors were also associated with coparenting behaviors observed during 3-months-play and 12-months-mealtime interactions and predicted unique variance in postpartum coparenting. Surprisingly, prenatal coparenting representations were not associated with prenatal behaviors, though representations and behaviors were associated at 3 months postpartum. Findings suggest that the coparenting relationship originates during pregnancy with prenatal coparenting representations and behaviors bridging the gap across the transition to coparenthood. Future studies should include assessments of both cognitive and behavioral facets of the prenatal coparenting relationship.